Q. 45.0( 3 Votes )

<span lang="EN-US

Answer :

We have, P (A B) = P (A)+ P (B)- P (A B)


From equation, =


P (B A) = × P (A) = 0.6× 0.4


= 0.24


Hence, = =


= 0.3 (answer)


And P (A B) = P (A)+ P (B)- P (A B)


= 0.4+0.8-0.24


= 0.96 (answer)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State True or FalMathematics - Exemplar

Fill in theMathematics - Exemplar

A speaks truth inMathematics - Board Papers

Often it is takenMathematics - Board Papers

Assume that each Mathematics - Board Papers

A bag X contains Mathematics - Board Papers